Systemic Risks in Global Banking : What Available Data Can Tell Us and What More Data Are Needed? - Cerutti, Eugenio (IMF Working Papers; Working Paper ;, 2011)
The recent financial crisis has shown how interconnected the financial world has become. Shocks in one location or asset class can have a sizable impact on the stability of institutions and markets around the world. But systemic risk analysis is severely hampered by the lack of consistent data that capture the international dimensions of finance. While currently available data can be used more effectively, supervisors and other agencies need more and better data to construct even rudimentary measures of risks in the international financial system. Similarly, market participants need better information on aggregate positions and linkages to appropriately monitor and price risks. Ongoing initiatives that will help in closing data gaps include the G20 Data Gaps Initiative, which recommends the collection of consistent bank-level data for joint analyses and enhancements to existing sets of aggregate statistics, and the enhancement to the BIS international banking statistics.